Effectiveness of Digital Pop-Up Book Science in Enhancing Students Critical Thinking Skills - Retno Yekti Utami; Sabar Nurohman; Pretty Oktianti Menur Kusuma Putri (Jurnal Pendidikan Sains Indonesia, 2025)
Critical thinking skills (CTS) are abilities that students must develop and enhance. This tudy aimed to examine the effectiveness of a digital pop-up book in science learning to enhance students CTS. The product was developed using the problem-based learning (PBL) model combined with a socio-scientific issue (SSI) approach, designed to connect science concepts with real-world contexts. The research employed a quasi-experimental method with a non-equivalent control group pretestposttest design, involving eighth-grade students at SMP Negeri 2 Manisrenggo. Data were collected through a critical thinking test consisting of 15 items covering four indicators: analyzing problems, identifying problems, formulating logical ideas, and drawing conclusions. Validation by experts indicated that the product was feasible for classroom use, while teacher and student evaluations confirmed its practicality and readability. The findings revealed that the experimental group achieved a higher average posttest score than the control group, with an N-gain of 0.37 (medium category), compared to 0.19 (low category) in the control group. The most significant improvement was observed in the ability to analyze and identify problems, whereas drawing conclusions showed limited progress. These results demonstrate that digital pop-up book media can serve as an effective learning tool to foster critical thinking by engaging students in authentic issues and collaborative problem-solving. The study suggests broader applications and future exploration of its long-term impact on critical thinking